The role of platelets in the pathogenesis of atherosclerosis - Tatyana O. Nikolaeva (Атеросклероз, 2021)
The participation of platelets in the development of atherothrombosis in acute forms of cardiovascular diseases is generally recognized and well studied, while their significance in the pathogenesis of vascular atherosclerosis, starting from the earliest stages, requires further study. This article analyzes the role of platelets in the pathogenesis of atherosclerosis. Modern views on the pathogenesis of atherosclerosis, platelet-endothelial interactions, molecular mechanisms of platelet activation, platelet immune function from the point of view of the initial stages of atherogenesis, studies of the effect of antiplatelet therapy in primary and secondary prevention of atherosclerosis are considered. The leading role of platelets in the inflammatory and immune reactions of the human body is indicated, which is realized due to a complex of immune receptors, adhesion molecules and mediators.